Recent developments on the cyclic stability in elastocaloric materials - Muhammad Imran (Materials & Design, 2020)
Solid-state cooling based on elastocaloric effect (eCE), i.e., a temperature change coupled to an applied uniaxial stress in elastocaloric materials (eCMs), is an emerging refrigeration technology which has a great potential to replace the conventional vapor compression systems. The cyclic stability is vital during long term operation of cooling systems for real commercial applications. The multiple cycling under mechanical loading causes to produce structural and functional fatigue in eCMs. Recently, various feasible strategies, e.g., microalloying, toughening through texture, adjusting the compressive stress mode and grain refinement, etc., have been employed in shape memory alloys (SMAs) to enhance the working stability of eCMs. As structural–/functional fatigue is a crucial challenge for elastocaloric cooling that must be overcome to make the technology commercial, we summarize the state-of-the-art strategies to enhance the cyclic stability in numerous well-studied eCMs. The article elucidates the methodology of these approaches through tailoring the materials or composition, arresting the crack initiation via microstructural modifications and the influence of properties (i.e. ∆Tad) under the cyclic application of stresses. Finally, the current report provides a summary of directly measured adiabatic temperature change (∆Tad) for various eCE SMAs over multiple cycles.